2022
DOI: 10.3390/biomedicines10030618
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Mediated Inflammatory Responses of Alveolar Epithelial Cells: Implications for COVID-19 Lung Pathology

Abstract: Background. Clinical and experimental evidence point to a dysregulated immune response caused by SARS-CoV-2 as the primary mechanism of lung disease in COVID-19. However, the pathogenic mechanisms underlying COVID-19-associated ARDS (Acute Respiratory Distress Syndrome) remain incompletely understood. This study aims to explore the inflammatory responses of alveolar epithelial cells to either the spike S1 protein or to a mixture of cytokines secreted by S1-activated macrophages. Methods and Results. The exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…Similar results have been shown in vivo by Bronte et al, who reported a tendency of IL-8 plasma levels to increase after 7 d of treatment with baricitinib, despite an evident drop of IL-6 during the same time [ 29 ]. IL-8 expression in coronavirus infected cells has been reported under AP-1 control [ 47 ], and, similarly, we found the same transcription factor involved in IL-8 synthesis in epithelial A549 cells [ 48 ]. Given the primary role of this chemokine as a potent attractant for neutrophils [ 49 , 50 ], the inefficacy of baricitinib on IL-8 release could explain why the transendothelial migration of neutrophils in vitro is stimulated by the CM_S1 medium and unaffected by baricitinib.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results have been shown in vivo by Bronte et al, who reported a tendency of IL-8 plasma levels to increase after 7 d of treatment with baricitinib, despite an evident drop of IL-6 during the same time [ 29 ]. IL-8 expression in coronavirus infected cells has been reported under AP-1 control [ 47 ], and, similarly, we found the same transcription factor involved in IL-8 synthesis in epithelial A549 cells [ 48 ]. Given the primary role of this chemokine as a potent attractant for neutrophils [ 49 , 50 ], the inefficacy of baricitinib on IL-8 release could explain why the transendothelial migration of neutrophils in vitro is stimulated by the CM_S1 medium and unaffected by baricitinib.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to pro-inflammatory cytokine release, previous studies have reported that the NLRP3 inflammasome pathway activated by Spike S1 led to an increase in pro-inflammatory cytokine gene expressions, including NLRP3, IL-1β and IL-18 [ 34 , 35 , 36 , 37 ]. Thus, the effects of the C. petasites extracts, CpEE and CpEA, as well as hesperetin on NLRP3 , IL-1β , and IL-18 mRNA expressions in Spike S1-induced A549 cells, were also determined using RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…This could eventually lead to the chronic or sub-chronic systemic inflammation that was observed in COVID-19 patients during the post-infection phase [ 3 , 12 ]. With regard to our in vitro investigation of the SP-induced inflammatory mechanism, as well as the therapeutic potential of the C. petasites extract and its active compounds, we selected A549 cells as our cell culture model because ACE2-expressed airway epithelial cells were used in the experiments of previous studies that focused on SARS-CoV-2 infection and inflammation [ 35 , 36 , 37 ]. Accordingly, these aforementioned studies used the same A549 cells to represent the lower respiratory system or the alveolar epithelial cells that were induced by the spike glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the inflammatory response conditions in both A549 lung cells and PMAtreated THP-1 macrophages, we first determined the optimal time required for an inflammatory response upon SP induction. A concentration of SP at 100 ng/mL was chosen from the review literature of previous studies that were investigated on inflammatory responses in lung epithelial cells [7,36], monocytes, or macrophage cells [3,5]. This concentration was then confirmed in our own laboratory.…”
Section: Spike Glycoprotein S1 (Sp) Induced An Inflammatory Response ...mentioning
confidence: 99%